2022
DOI: 10.3390/s22239468
|View full text |Cite
|
Sign up to set email alerts
|

AI-Based Detection of Aspiration for Video-Endoscopy with Visual Aids in Meaningful Frames to Interpret the Model Outcome

Abstract: Disorders of swallowing often lead to pneumonia when material enters the airways (aspiration). Flexible Endoscopic Evaluation of Swallowing (FEES) plays a key role in the diagnostics of aspiration but is prone to human errors. An AI-based tool could facilitate this process. Recent non-endoscopic/non-radiologic attempts to detect aspiration using machine-learning approaches have led to unsatisfying accuracy and show black-box characteristics. Hence, for clinical users it is difficult to trust in these model dec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, there are few studies that analyze video images with AI and use them to diagnose diseases. Konradi et al [ 24 ] developed explainable artificial intelligence (XAI) to analyze Flexible Endoscopic Evaluation of Swallowing (FEES) videos. In this pilot study, it was reported that the accuracy of the training data was 0.925 and the testing data was 0.571 to diagnose swallowing disorders [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few studies that analyze video images with AI and use them to diagnose diseases. Konradi et al [ 24 ] developed explainable artificial intelligence (XAI) to analyze Flexible Endoscopic Evaluation of Swallowing (FEES) videos. In this pilot study, it was reported that the accuracy of the training data was 0.925 and the testing data was 0.571 to diagnose swallowing disorders [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Konradi et al [ 24 ] developed explainable artificial intelligence (XAI) to analyze Flexible Endoscopic Evaluation of Swallowing (FEES) videos. In this pilot study, it was reported that the accuracy of the training data was 0.925 and the testing data was 0.571 to diagnose swallowing disorders [ 24 ]. Similar to this study, Jeong et al [ 25 ] attempted to diagnose swallowing disorders using VFSS video with the ResNet3D AI model.…”
Section: Discussionmentioning
confidence: 99%